Ethnic variations in warfarin pharmacogenetics: A comprehensive review - Gulnara Svyatova, Yergali Miyerbekov, Galina Berezina, Alexandra Murtazaliyeva, Rustem Tuleutayev (Journal of Applied Pharmaceutical Science, 2025)
The therapeutic dose of warfarin depends more on the patient’s genotype than on the type of disease. However, to date, no uniform algorithms have been developed for warfarin dosing in different nationalities. Hence, the study aims to evaluate and structure existing recommendations for warfarin prescription in different nations. A systematic search for the necessary information for 2011–2023 on the dosage of warfarin in different ethnic groups was conducted. The databases used for this search are PubMed, Embase, Scopus, Google Scholar, and Web of Science. The correlation between various genetic polymorphisms and the pharmacodynamics and pharmacokinetics of warfarin was revealed. This primarily refers to the presence of genes of the cytochrome P450 family and vitamin K epoxide reductase complex 1. At the same time, the necessity of studying the genes CYP2C19, and gamma-glutamyl carboxylase (GGCX) is discussed. These genes can significantly improve the accuracy of existing pharmacogenetic algorithms, although they may slightly increase the individual variability of warfarin dosing.
Keywords: Genotype, genetic polymorphism, cytochrome, pharmacodynamics, algorithm